EFEK MEDIASI INTERNET REPORTING OF STRATEGIC INFORMATION ATAS PENGARUH KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP KINERJA KEUANGAN - Yosep Fangohoi; Tigor Sitorus (Jurnal Manajemen, 2018)
In corporate governance, the role of independent commissioners and audit committees is very important in ensuring that all operational and strategic activities are going well because they greatly affect the financial performance of the entity. This study aims to empirically analyze the influence of independent commissioners and audit committees on financial performance and whether the existence of strategic information disclosure through the internet (IRSI) is able to mediate independent commissioners and audit committees on financial performance to be better or vice versa in banking companies. The population in this study are companies listed on the Indonesia Stock Exchange in 2014-2016. The data obtained is secondary data. Data analysis using WarpPLS 3.0 program with statistical models, which is Structural Equation Modeling Analysis (SEM). The results of the study indicate that independent commissioner variable has no significant effect on financial performance, but on the contrary the audit committee variable has a significant impact on financial performance. In addition, independent commissioner variable has no significant effect on the internet reporting of strategic information (IRSI), but audit committee variable has a significant effect on IRSI. The IRSI variable has a significant influence on financial performance. The conclusions of mediation show that IRSI was able to mediate the audit committee on financial performance but IRSI was unable to mediate independent commissioner variables on financial performance.